The within-task criterion to determine successful and unsuccessful table tennis players - Piras, A.; Lanzoni, I. M.; Raffi, M.; Persiani, M.; Squatrito, S. (International Journal of Sports Science & Coaching, 2016)
The aim of this study was to examine the differences in visual search behaviour between a group of expert-level and one of novice table tennis players, to determine the temporal and spatial aspects of gaze orientation associated with correct responses. Expert players were classified as successful or unsuccessful depending on their performance in a video-based test of anticipation skill involving two kinds of stroke techniques: forehand top spin and backhand drive. Eye movements were recorded binocularly with a video-based eye tracking system. Successful experts were more effective than novices and unsuccessful experts in accurately anticipating both type and direction of stroke, showing fewer fixations of longer duration. Participants fixated mainly on arm area during forehand top spin, and on hand-racket and trunk areas during backhand drive. This study can help to develop interventions that facilitate the acquisition of anticipatory skills by improving visual search strategies. ABSTRACT FROM AUTHOR